Continuing need for and provision of a service for non-standard implant removal. Issue 2 (30th September 2013) - Pillai, Mary; Gazet, A Caroline; Griffiths, Megan
Abstract : Background and methodology: Information is presented on the management of women referred to a sexual health service during a 1-year period for management of a non-palpable contraceptive implant or of a palpable implant considered unsuitable for routine removal. Results: Fifty-two women were referred. Thirty-four implants were non-palpable and their depth on ultrasound ranged from 2.7 to 12 mm. Seventeen were fully or partly palpable and their depth ranged from 3 mm or less (16 cases) to 5.6 mm (one case). Nine had had previous failed attempts at removal, including three with two previous failed attempts. Three implants were located at sites other than the medial aspect of the arm, and were associated with long localisation times. Forty-seven implants were removed at a one-stop clinic appointment through a 2–3 mm incision using ring forceps. The mean time for removal from making the incision to complete extraction was 4.8 minutes. Three cases judged to be of higher risk were removed under local anaesthesia in theatre through a 15 mm incision. These included the only case where removal was attempted unsuccessfully in the outpatient clinic. Seven of the implants were Nexplanon ®, including four cases seen during the last month of data collection. Conclusions: Removal with the technique described is rapid, with an average time of 4–5 minutes, and less than 10 minutes in >90% of cases. Preliminary indications suggest that the introduction of Nexplanon has not resolved the problem of deep implant insertion. Based on our experience we suggest criteria for centres providing removal of deep implants.